2021
DOI: 10.1016/j.frl.2021.101940
|View full text |Cite
|
Sign up to set email alerts
|

Global financial crisis and COVID-19: Industrial reactions

Abstract: We study industrial reactions to both the global financial crisis of 2008 and the COVID-19 pandemic. Although most industries in the U.S. suffered from the two events, the stock performance of most industries started to recover following the announcements of quantitative easing. Our results indicate that quantitative easing is effective in boosting investor confidence. We also find that the effect of quantitative easing in 2020 on stock performance is more significant for the industries that are more affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 17 publications
0
45
0
1
Order By: Relevance
“…A worldwide economic and financial crisis has followed the COVID-19 pandemic, overwhelming the 2008-2010 crisis (Brada et al, 2021;Chen & Yeh, 2021;Gromski et al, 2021). Research has indicated that families prefer to reduce their spending on products and services that are not needed until the economy recovers again Kumar & Shah, 2021;Soon et al, 2021).…”
Section: Strategies For Financial Recoverymentioning
confidence: 99%
“…A worldwide economic and financial crisis has followed the COVID-19 pandemic, overwhelming the 2008-2010 crisis (Brada et al, 2021;Chen & Yeh, 2021;Gromski et al, 2021). Research has indicated that families prefer to reduce their spending on products and services that are not needed until the economy recovers again Kumar & Shah, 2021;Soon et al, 2021).…”
Section: Strategies For Financial Recoverymentioning
confidence: 99%
“…Many small firms suffered large decreases in demand, were unable to organize work remotely using technology, and did not have sufficient room for social distancing. 3 Those in certain industries, such as hospitality and construction were particularly hard hit (e.g., Chen and Yeh, 2020), as were those in states with the strictest lockdowns (e.g., Goel and Thakor, 2020;Hale, Petherick, Phillips, and Webster, 2020). As discussed further in Section 3, there was an "economic surprise" in which the recession caused by the public health crisis was very short and the economic recovery was quite extraordinary.…”
Section: The Covid-19 Crisismentioning
confidence: 99%
“…Many companies are choosing cost cutting strategies to survive the economic shocks caused by the Covid-19 pandemic. Likewise in the USA, a recent study by (Chen & Yeh, 2021) concluded that the Covid-19 pandemic caused financial performance and stock prices as measured by CAR in 49 industries listed on the New York Stock Exchange to experience a negative even. However, efforts through quantitative easing can restore investor confidence and improve stock performance.…”
Section: Introductionmentioning
confidence: 99%